(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The five main strains of the Hepatitis Virus lead to inflammation of the liver, along with a wide range of health problems, that can potentially be fatal (“Hepatitis”). The five main strains of the Hepatitis Virus are A, B, C, D, and E, that consist of a similar target organ but differ in types of symptoms, side effects, mode of transport, and treatments. The main hepatitis related deaths are through liver cirrhosis, Hepatocellular Carcinoma (liver cancer), and Fibrosis, which are most commonly caused by chronic Hepatitis B and C. In the United States, over 3.5-5.3 million individuals live with the chronic strand of viral Hepatitis, in which symptoms are suppressed until severe liver damage has occurred (Liang). The liver is an essential organ that is required to filter blood, detoxicate the system, and absorb vital nutrients for healthy function of the body. Hence, damage to the liver prevents quintessential functions from occurring. While hepatitis or damage to the liver can be caused by various ways of intoxicating the system such as excessive alcohol intake or medication, the more severe and direct method is through the infection of the Hepatitis B or Hepatitis C viral strand. While both chronic viruses cause hepatitis, the manifestation, mode of transport, severity, and treatments can defer vastly. With this in mind, the most effective methods of research in this field are done through the use of In-Vivo Model Systems for Hepatitis. In-Vivo systems include